Location-based Questions: Types and Implications for Consortial Reference Services - Bishop, Bradley Wade (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper explores location-based questions asked to a statewide consortial reference service. Literature assumes that non-local librarians would have difficulty responding to questions about places beyond their own library. Based upon the types of questions asked, non-local librarians would benefit from additional local knowledge added to their participating libraries' websites. Cette communication explore les questions géodépendantes posées à un consortium de service de référence offert à l’échelle d’un État. La littérature suppose que les bibliothécaires distants ont plus de difficulté à répondre aux questions non locales. Selon le type de questions posées, les bibliothécaires distants tireraient profit d’un ajout d’information locale sur le site Web des bibliothèques participantes.